The Impact of Emissions Trading Program on the Labor Demand of Enterprises: Evidence From China - Wang, Chang’an; Liu, Xiaoqian; Xi, Qian; Zhang, Ying (Frontiers in Environmental Science, 2022)
The emissions trading program (ETP) is an effective means to fight environmental pollution. However, it may also spur the increase of enterprise costs, which affects employment and economic development. Adopting a difference-in-differences method and exploiting China’s emissions trading policy in 2007 as a quasi-natural experiment, we investigate the impact of the ETP on firms’ labor demand and the mechanism facilitating this effect. The results show that the ETP significantly reduces firms’ labor demand. The conclusion remains robust after using an instrumental variable to alleviate the possible endogeneity problem. Mechanism analysis indicates that the ETP reduces firms’ labor demand via increasing firms’ environmental expenditure and reducing profits. The heterogeneity analysis shows that the ETP significantly reduces the labor demand of SO2 emitting firms and heavy polluting firms, while having no significant impact on the labor demand of non-SO2 emitting firms and non-heavy polluting firms. This negative impact is more prominent for resource-based cities and old industrial base cities. This paper provides empirical evidence and policy implications for implementing the ETP in developing countries.